1965
DOI: 10.1152/ajplegacy.1965.209.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of removal of calcium from bathing media on frog stomach

Abstract: Removal of Ca++ from the solutions bathing the frog gastric mucosa results in an initial increase in resistance (first phase) and a subsequent marked decrease in resistance (second phase). During the first phase the H+ secretory rate is decreased by 39% and the potential difference (PD) by 10%. During the second phase the measured H+ rate decreased to zero and the PD to near zero. Anoxia or DNP, which ordinarily produce a marked increase in resistance, failed to do so in the absence of Ca++. Comparable effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

1973
1973
1989
1989

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…However the role of calcium in isolated gastric secretion is far from being elucidated. Apparently a direct correlation between calcium and gastric secretion was found by some authors [29,30] whereas the opposite was true in other studies [31,32]. Our experiments did not throw light on this complex problem inasmuch as Ca++-free solution decreased gastric secretion and ionophore A 23187 increased it; on the other hand drugs interfering at different levels with calcium ions were virtually ineffective.…”
Section: Discussioncontrasting
confidence: 75%
“…However the role of calcium in isolated gastric secretion is far from being elucidated. Apparently a direct correlation between calcium and gastric secretion was found by some authors [29,30] whereas the opposite was true in other studies [31,32]. Our experiments did not throw light on this complex problem inasmuch as Ca++-free solution decreased gastric secretion and ionophore A 23187 increased it; on the other hand drugs interfering at different levels with calcium ions were virtually ineffective.…”
Section: Discussioncontrasting
confidence: 75%
“…A calcium requirement for gastric acid secretion has also been demonstrated (Forte & Nauss, 1963;Jacobson, Schwartz & Rehm, 1965). The cause of inhibition in these and other electrolyte transport processes is difficult to assess.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the frog gastric mucosa like the frog cornea actively transports C1-. Secondly, it had previously been shown that Ca2+ appears to be essential for the normal functioning of the acid secretory mechanism (12,13). The results of the present investigation with Ca ionophore A23187 are described herein.…”
mentioning
confidence: 69%